The Methyl-CpG Binding Protein MBD1 Interacts with the p150 Subunit of Chromatin Assembly Factor 1 - Reese, Brian E. (American Society for Microbiology, 2003)
DNA promoter hypermethylation has been shown to be a functional mechanism of transcriptional repression. This epigenetic gene silencing is thought to involve the recruitment of chromatin-remodeling factors, such as histone deacetylases, to methylated DNA via a family of proteins called methyl-CpG binding proteins (MBD1 to -4). MBD1, a member of this family, exhibits transcription-repressive activity, but to this point no interacting protein partners have been identified. In this study, we demonstrate that MBD1 partners with the p150 subunit of chromatin assembly factor 1 (CAF-1), forming a multiprotein complex that also contains HP1α. The MBD1-CAF-1 p150 interaction requires the methyl-CpG binding domain of MBD1, and the association occurs in the C terminus of CAF-1 p150. The two proteins colocalize to regions of dense heterochromatin in mouse cells, and overexpression of the C terminus of CAF-1 p150 prevents the targeting of MBD1 in these cells without disrupting global heterochromatin structure. This interaction suggests a role for MBD1 and CAF-1 p150 in methylation-mediated transcriptional repression and the inheritance of epigenetically determined chromatin states.